Emerging and persistent inorganic contaminants in prioritized foods: results from Portuguese Total Diet Pilot Study - Ventura, Marta (2018)
Total diet studies (TDS) provide analytical data to estimate dietary exposure and risk assessment of contaminants. TDS were adopted by several European countries as the sound scientific basis for strength the linkage between food consumption and food analysis with the purpose to assess the effect of harmful substances on health. Heavy metals have been extensively studied and their effects on human health regularly reviewed by international bodies such as the World Health Organization (WHO). Bromine is a halogen of emerging concerned and has been associated with endocrine disruption and subject to bioaccumulation in food chains. The aim of this work was to study the profile of chemical contaminants; lead chromium, cadmium. Arsenic and bromine as a contaminant of emerging concerned in foods collect in Portuguese TDS pilot study. Four hundred and eighty foods were purchased and prepared as consumed were pooled in forty laboratory samples. Then were digested with concentrated nitric acid and hydrogen peroxide in a microwave system for Pb, Cr, Cd and As, total bromine was determined using tetramethyl ammonium hydroxide (TMAH) extraction. Digested samples were analysed by inductively coupled plasma mass spectrometry (ICP-MS) and HPLC-ICP-MS for total and chemical species respectively. Analytical procedures were carried out under rigorous metrological control, laboratory performance was demonstrated through a successful participation in PT schemes runs by an accredited provider. The decreasing sequence of the mean inorganic contaminants in prioritised foods was as follows: As > Br > Cr > Pb > Cd. In Octopus was found the highest amount of As, 9138 ± 237 μg/kg, mainly arsenobetaine and in clams were detected the highest concentrations of Cd and Pb, 125 ± 17 μg/kg and 260 ± 23 μg/kg, respectively. The results of TDS Portuguese Pilot study showed that contents of inorganic chemical contaminants are similar to those published by studies carried out in other European Countries. Based on studies published we can inferred that intake of inorganic substances do not pose a risk to Portuguese population.